Candidate gene study reveals DRD1 and DRD2 as putative interacting risk factors for youth depression - Corrales Acuña, Eyleen Vanessa (2016)
Alterations in the monoaminergic neurotransmission systems are suspected to be involved in the etiology of neuropsychiatric disorders, including depression. The role of these pathways in the risk of developing depressive symptoms during childhood or adolescence is still not completely clear. This study sought to identify putative genetic factors in genes of serotonergic and dopaminergic systems mod- ulating the level of manifestation of depressive symptoms in children and adolescents. We analyzed 170 single nucleotide polymorphisms (SNPs) in 21 candidate dopaminergic and serotonergic genes in a non- clinical sample of 410 Costa Rican participants of ages between 7 and 18 years, assessing the severity of depressive symptoms through the Child Depression Inventory (CDI). Genotypic and haplotypic associa- tions, as well as epistatic effects, were examined. A signi fi cant interaction effect was detected between rs1039089 in conjunction with rs877138 located upstream of the dopamine D1 receptor ( DRD1 ) and the dopamine D2 receptor ( DRD2 ) genes respectively, although no evidence was found for any single variant or haplotype related to a differential liability. This newly described genetic interaction among putative regulatory regions of dopamine receptors could affect the level of manifestation of depressive symptoms through an imbalance of D1-D2 heteromers and modulation of cognitive processes